Systematic analysis on multiple Gene Expression Omnibus data sets reveals fierce immune response in hepatitis B virus‐related acute liver failure. Issue 17 (19th July 2020) - Chen, Huadi; Zhao, Wenting; Zhang, Yixi; Guo, Yiwen; Luo, Weixin; Wang, Xiaobo; Nie, Yu; Ye, Maodong; Huang, Changjun; Wang, Dongping; Chen, Maogen; He, Xiaoshun; et al.
Abstract: Acute liver failure (ALF) caused by hepatitis B virus (HBV) is common type of liver failure in the world, with high morbidity and mortality rates. However, the prevalence, genetic background and factors determining the development of HBV‐related ALF are rarely studied. In this study, we examined three Gene Expression Omnibus (GEO) data sets by bioinformatics analysis to identify differentially expressed genes (DEGs), key biological processes and pathways. Immune infiltration analysis showed high immune cells infiltration in HBV‐related ALF tissue. We then confirmed natural killer cells and macrophages infiltration in clinical samples by immunohistochemistry assay, implying these cells play a significant role in HBV‐ALF. We found 1277 genes were co‐up‐regulated and that 1082 genes were co‐down‐regulated in the 3 data sets. Inflammation‐related pathways were enriched in the co‐up‐regulated genes and synthetic metabolic pathways were enriched in the co‐down‐regulated genes. WGCNA also revealed a key module enriching in immune inflammation response and identified 10 hub genes, differentially expressed in an independent data set. In conclusion, we identified fierce immune inflammatory response to elucidate the immune‐driven mechanism of HBV‐ALF and 10 hub genes based on gene expression profiles.